Internet use and self-reported health problems among secondary school students in Kwara State Nigeria (2013)
The internet has consistent positive impacts on modem society, it has also caused various societal concerns about privacy, security, pornography, internet crime, and health related problem. Its easy accessibility poses greater risks and dangers for adolescents as compared to other forms of media. This study investigated internet use and self reported health problems among secondary school students in Ilorin South Local Government Area of Kwara State. The study is a descriptive survey and a self developed questionnaire with reliability coefficient of 0.71 was used as instrument for data collection. One thousand and twenty (1020) respondents were selected using purposive and simple random sampling technique from 17 public schools. One research question and one hypothesis were raised. The data was analysed using percentages for the research questions and inferential statistics of regression to test the hypotheses at 0.05 alpha level. The results shows that internet use is independently related with risky sexual behaviour having the greatest contribution of 52.4% (β=.524, t=20.752, p<0.05), followed by eating disorder with 49.1% (β=.491, t=18.015, p<0.05), then depression with 32.1 (β=.321, t=16.27, p<0.05), while sleeping disorder has the least contribution of the independent variables on the dependent variable (F(4,1015)=15.076, p<0.05). The study concluded that there is a significant relationship between all the independent variables and the dependent variable. In recommendation, parents and teachers should device appropriate skills in building a broad knowledge base necessary to deal with adolescents' use of internet; they should be exposed to other creative and interesting activities beyond internet use.